THE EFFECT OF COMPLAINT HANDLING, SERVICE FACILITIES AND SERVICE LOCATION ON CUSTOMER SATISFACTION AT PUBLIC HEALTH CENTERS - Sri Rejeki; Aceng Abdul Hamid (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — This research is to find out and test the influence of complaint handling, service facilities and service location on customer satisfaction in Public Health Centers.Research method — Study this is study quantitative with Regression. Study this use approach quantitative for see connection causality from a number of influencing factor _ to Satisfaction Customer . Population in study this is Patients at the Kramat Public Health Center, Tegal Regency, Central Java Province, totaling 95 respondents. Data collected with questionnaire and study document, after that's the data in the validity test as well as reliability.Result— Research results show that Handling Complaints, Facilities Service, and Service Location take effect to Satisfaction Customer by simultaneous. From value data _ adjusted R Square of 0.533, this means by together effect of variable X 1 , X 2 , and X 3 is 53.3% against change Y or in other words influence variable free (Handling Complaints, Facilities Service , Service Location) to variable bound ( Satisfaction customers) by 53.3 % while the rest that is 46.7 % caused by other variables that do not enter researched in framework research .With thereby factor handler Complaints, Facilities Service , Service Location must Keep going maintained and if need more upgraded again . So that service to Public in accordance with what is expected by the government and society as user service service health.Conclusion— Based on results observation writer at health center District Kramat Tegal that from aspect handling complaint that is, the lack of clear information from officer health so that impact Public health center in Thing this no knowing what 's missing in To do Health services to society. Of the nine elements survey in questionnaire, that is, what is delivered to community / customer Public health center Kramat, District Tegal, there are element that gets highest SME score that is element cost affordable service. Meanwhile elements that are still many complain Public that is element Handling complaint.